Segmentation and Targeting Strategy Socialization at ‘Tempe SS’ as Business Unit of Sirajussa’adah Islamic Boarding School in Limo, Depok, West Java (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Businesses must be able to carry out marketing activities effectively. Some marketing activities that must be implemented effectively are segmentation, targeting, and positioning strategies. Tempe SS  stands for Tempe Santri Sirajussa’adah, one of the Business Unit’s brands at the Sirajussa'adah Islamic Boarding School. It is considered one of the micro-scale businesses in the Limo Depok area. Even though they have carried out the production process for product distribution and marketing activities, it is still not financially independent and relies on donations. The priority problem based on the discussions is the lack of knowledge and skills in marketing segmentation and targeting strategies. Socialization regarding digital knowledge and segmentation and targeting strategies were conducted in two steps. The first was related to digital marketing material, and it continued with socialization on segmentation and targeting strategy. The analysis results of the segmentation and targeting strategy socialization activities were recorded as increasing partners' understanding of digital marketing by 61.68% and increasing partners' knowledge of segmentation and targeting strategy by 72.68%. In other words, this community service was able to have an impact on the increasing understanding of Partners beyond the initial target expected. This result is expected to help the management of the Tempe SS business unit increase its business income and scale from 'micro' status to 'small' business.